The transformation of dominant parties in Asia: Introduction to the special issue. Issue 1 (March 2019) - Kasuya, Yuko; Sawasdee, Siripan Nogsuan
Dominant political parties have been the subject of study since the 1950s. As they have emerged both in democracies and non-democracies, they have become an intriguing research theme for scholars who study politics in a variety of world regions. This introductory note to the special issue on the transformation of dominant parties in Asia first reviews how "dominant parties" are defined by scholars who study this subject. Then, it turns to a discussion of the existing research on dominant parties and analyzes how scholars have examined the question of how they emerge and are sustained. Lastly, the articles included in this special issue are introduced.